Asuhan Keperawatan pada Pasien Respiratory Distress of Newborndengan Pemberian Posisi Quarter Prone (IJM: Journal of Multidisiplinary, 2025)
Respiratory Distress of Newborn (RDN) is a condition of respiratory distress that often occurs in newborns, especially in premature babies, which is characterized by difficulty breathing, chest retraction, and use of accessory respiratory muscles. This position is known to increase oxygenation and reduce the workload of breathing in neonates with respiratory disorders. This study aims to describe the provision of a quarter prone position in nursing care for By.VI aged 1 day with a medical diagnosis of respiratory distress of newborn in the NICU Room of Dr. Zainoel Abidin General Hospital Banda Aceh. The method used in this study is a case study approach with the application of the quarter prone position as part of the nursing care given to the patient. The data collected included observations of vital signs, respiratory rate, oxygen saturation, and the baby's response to the position. The results of the study showed an improvement in the baby's respiratory condition after being given the quarter prone position, which was marked by stabilization of respiratory rate and increased oxygen saturation. The quarter prone position helps reduce pressure on the baby's chest and increases lung expansion, thereby improving ventilation and lung perfusion. The conclusion of this study is that providing the quarter prone position can be one of the effective non-pharmacological interventions in nursing care for babies with Respiratory Distress of Newborn.